A metasurface enabled dual band antenna exhibiting dual polarizations with reduced beam squint and cross polarization. Issue 12 (20th October 2022) - Jash, Shyam Sundar; Ghatak, Rowdra
Abstract: A compact, dual‐band metasurface‐based microstrip patch antenna with both linear and circular polarization (CP) for multiband communication is reported in this work. The ingredients in the antenna design consist of a combination of metasurface and metamaterial inspired structures that are demonstrated as an effective technique to correct the beam squint problem and reduce the cross‐polarized radiation, usually experienced by thick substrate‐based broadband CP antennas. A fractal boundary metasurface is introduced to achieve CP over a small frequency band. Eight Electric‐LC resonators are symmetrically placed in the same plane of the radiating patch to widen the CP bandwidth, correct the beam squint, reduce the cross‐polarized radiation, and realize a subwavelength resonance of λ0 /5.15 order. The measured impedance bandwidths (|S11 | < −10 dB) of the proposed antenna are 7.8% (3.7–4.0 GHz) and 27.58% (5.05–6.65 GHz) in the lower and upper‐frequency band, respectively. The measured 3‐dB axial ratio bandwidth (ARBW) is 24.8% (5070–6510 MHz) at 5.8 GHz. The fabricated prototype has an overall size of 55 × 55 × 4.08 mm (0.696λ0  × 0.696λ0  × 0.051λ0 at 3.8 GHz or 1.063λ0  × 1.063λ0  × 0.078λ0 at 5.8 GHz) with a realized peak gain of 4 dBi in the lower band and 7.1 dBic in the upper band. The measured results are consistent with the simulation results.